In vitro antiradical and neuroprotective activity of polyphenolic extract from marine algae Padina australis H. - Murugan, Amarchand Chordia; Vallal, Dahineeswari; Karim, Md. Rezaul; Govindan, Natanamurugaraj; M. M., Yusoff; Rahman, Md. Mokhlesur (JOCPR, 2015)
The neuroprotective properties and antioxidant potential of polyphenolic extracts from a brown seaweed Padina australis, were evaluated by the inhibition assay against acetylcholine esterase using indoxyl acetate as the substrate, and by the radical scavenging activity assay against 1,1-diphenyl-2-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), and ferrous ion chelating (FIC) activity assay. Methanolic (80%) crude extracts was fractionated by different solvent partitioning, and the assays of each fraction were performed using the microplate reader. The highest total phenolic content (TPC) was observed in n-butanol soluble fraction with a value of 188.75±0.21 mg GAE/g. In addition, the n-butanol soluble fraction showed the highest ferric reducing power (188.34±0.15 mg GAE/g) and the highest ferrous ion chelating ability (76.52±0.12%). The highest free radical scavenging activity against DPPH was found in water soluble fraction with 77.5±1.82% inhibition. However, the βcarotene bleaching activity was found higher with the non-polar solvent, n-hexane extract (58.12±0.58%). A strong positive correlation was found between the total phenolics and antioxidant activities of the fractions. Acetylcholinesterase (AChE) inhibitory properties of all the fractions were assayed where n-butanol soluble fraction was found to have better AChE inhibitory activity (57.94±0.17%) with an IC50 value of 1.54±0.045 mg/ml. The results suggested that the polar fractions possess higher AChE inhibitory and antioxidant activity. It can be concluded that Padina australis possesses an appreciable amount of polyphenols with notable antioxidant and antiAChE properties that could be promisingly used in the treatment of neurodegenerative disorders.